2022
DOI: 10.3390/jof8050463
|View full text |Cite
|
Sign up to set email alerts
|

The Arf-GAP Proteins AoGcs1 and AoGts1 Regulate Mycelial Development, Endocytosis, and Pathogenicity in Arthrobotrys oligospora

Abstract: Small GTPases from the ADP-ribosylation factor (Arf) family and their activating proteins (Arf-GAPs) regulate mycelial development, endocytosis, and virulence in fungi. Here, we identified two orthologous Arf-GAP proteins, AoGcs1 and AoGts1, in a typical nematode-trapping fungus Arthrobotrys oligospora. The transcription of Aogcs1 and Aogts1 was highly expressed in the sporulation stage. The deletion of Aogcs1 and Aogts1 caused defects in DNA damage, endocytosis, scavenging of reactive oxygen species, lipid dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 76 publications
(106 reference statements)
0
6
0
Order By: Relevance
“…Moreover, several genes associated with lipids, actin, growth, the MAPK pathway, vesicles, cell fusion, and TCA cycles were significantly enriched and consistent with phenotypic traits. For example, G protein complex alpha subunit and cell division control protein Cdc42 have been proven to play a crucial role in mycelial growth, conidiation, trap formation, and stress response in A. oligospora ( 11 , 49 ). Meanwhile, Ssk2 and Ste50 are indispensable components of the MAPK signaling cascade and have been reported to be involved in growth, conidiation, stress response, and virulence in A. oligospora and other pathogenic fungi ( 32 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several genes associated with lipids, actin, growth, the MAPK pathway, vesicles, cell fusion, and TCA cycles were significantly enriched and consistent with phenotypic traits. For example, G protein complex alpha subunit and cell division control protein Cdc42 have been proven to play a crucial role in mycelial growth, conidiation, trap formation, and stress response in A. oligospora ( 11 , 49 ). Meanwhile, Ssk2 and Ste50 are indispensable components of the MAPK signaling cascade and have been reported to be involved in growth, conidiation, stress response, and virulence in A. oligospora and other pathogenic fungi ( 32 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of trap regulation will lead to comprehensive understandings of how cell types transform and why NT fungi have co-evolved with the emergence of nematodes. Over the past decade, G-protein-associated signaling has been considered the main explanation underlying the trap formation [23, 41, 42]. Multi-omics analysis commonly revealed that the membrane biogenesis-associated pathways contribute to trap formation [43].…”
Section: Discussionmentioning
confidence: 99%
“…Cellular ROS accumulation in the fungal hyphae was determined by dihydroethidium (DHE) (Beyotime, Shanghai, China) staining. Briefly, the collected mycelia were mixed with 10 μg/mL DHE solution, incubated at 37°C for 30 min, and then washed with phosphate-buffered saline (PBS) twice ( 62 ). Subsequently, ROS levels were estimated from the intensity of DHE fluorescence with the same weight of mycelium via multimode microplate reader (Molecular Devices, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%